Analisis Pengaruh Pertumbuhan Ekonomi, Pembangunan Manusia, dan Ketimpangan Pendapatan terhadap Kemiskinan di Kota Jambi Periode 2016-2024 - Nasywa Azzahra Putri; Nadzira Alya Khairunnisa; Arina Romarina (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the influence of economic growth, human development, and income inequality on poverty in Jambi City for the period 2016-2024. Using multiple linear regression method with secondary data from BPS Jambi City, this research examines the relationship between GRDP per capita, Human Development Index (HDI), and Gini Ratio on poverty percentage. The analysis results show that the model has an R Square of 0.566 or 56.6%, but the model as a whole is not significant (Sig. F = 0.210). Classical assumption tests indicate that residuals are normally distributed (Sig. K-S = 0.200) and there is no heteroscedasticity or autocorrelation. However, serious multicollinearity problems were found in GRDP per capita (VIF = 11.686) and HDI (VIF = 10.658) variables, indicating that both variables are highly correlated. Data trend analysis shows a decrease in poverty percentage from 8.87% (2016) to 7.73% (2024), although it surged to 9.02% in 2021 due to the COVID-19 pandemic. GRDP per capita experienced 63.3% growth during the research period, while HDI increased from 76.14 to 81.04. The Gini Ratio showed a fluctuating trend with the highest value of 0.40 in 2024. These findings indicate a trade-off between economic growth and income inequality in Jambi City.